Association of dyslipidaemia with osteoporosis in postmenopausal women. Issue 3 (March 2021) - Zhang, Lingnan; Liu, Qilong; Zeng, Xianshang; Gao, Wenshan; Niu, Yanan; Ma, Xiaoyong; Xie, Huijun; Zhou, Xiaozhe; Yu, Weiguang; Xu, Guixing
Objective: To assess the association of dyslipidaemia with osteoporosis in postmenopausal women. Methods: Data from 160 postmenopausal women with newly diagnosed osteoporosis (osteoporosis group) and 156 healthy controls (control group) were retrospectively reviewed from 2016 to 2020. The primary outcomes were laboratory values assessed by a multivariate binary logistic regression model. Results: Factors that greatly increased the risk of being in the osteoporosis group included high low-density lipoprotein (LDL) and low high-density lipoprotein (HDL) levels. The osteoporosis group had lower HDL and higher LDL levels than the control group. A multivariate binary logistic regression model showed that lower HDL and higher LDL levels were the only variables that were significantly associated with osteoporosis (odds ratio 1.86, 95% confidence interval: 3.66–4.25 and odds ratio 1.47, 95% confidence interval: 1.25–2.74, respectively). Conclusion: Low HDL and high LDL levels may be associated with the occurrence of osteoporosis in postmenopausal women.